1996
DOI: 10.1021/es950397k
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Metal−Nitrilotriacetate Complexes by Chelatobacter heintzii

Abstract: Nitrilotriacetic acid (NTA) is a synthetic chelating agent that can form strong water-soluble complexes with a wide range of radionuclide and metal ions and has been used to decontaminate nuclear reactors and in the processing of nuclear materials. The co-disposal of NTA or other synthetic chelating agents with radionuclides may result in increased dispersal of radionuclides in soil and subsurface environments. Understanding the influence of aqueous geochemistry on NTA degradation is essential to predict the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 50 publications
5
67
1
Order By: Relevance
“…146,156 showed that citrate was degraded by P. fluorescens to the point where the ligand-to-metal ratio reached 1:1 in Cu-citrate and 2:3 in U-citrate systems, while degradation of citrate in the presence of other metals proceeded to completion, although at a lower rate than in systems with no significant metal concentrations. Similar results were seen by BOLTON et al 163 for NTA degradation in the presence of metals. In actinide systems, BANASZAK et al 116 showed that NTA degradation in the presence of Np(V) went to completion in the absence of metal toxicity effects, while REED et al 165 found that the degradation rate of NTA in the presence of Pu(IV), which has a NTA complex formation constant six to seven orders of magnitude greater than that of Np(V)-NTA, was significantly decreased, but not stopped, as the ligand-to-metal ratio approached 1 : 1.…”
Section: Effect Of Actinides On Organic Speciation and Bioavailabilitysupporting
confidence: 90%
See 3 more Smart Citations
“…146,156 showed that citrate was degraded by P. fluorescens to the point where the ligand-to-metal ratio reached 1:1 in Cu-citrate and 2:3 in U-citrate systems, while degradation of citrate in the presence of other metals proceeded to completion, although at a lower rate than in systems with no significant metal concentrations. Similar results were seen by BOLTON et al 163 for NTA degradation in the presence of metals. In actinide systems, BANASZAK et al 116 showed that NTA degradation in the presence of Np(V) went to completion in the absence of metal toxicity effects, while REED et al 165 found that the degradation rate of NTA in the presence of Pu(IV), which has a NTA complex formation constant six to seven orders of magnitude greater than that of Np(V)-NTA, was significantly decreased, but not stopped, as the ligand-to-metal ratio approached 1 : 1.…”
Section: Effect Of Actinides On Organic Speciation and Bioavailabilitysupporting
confidence: 90%
“…225 When other, non-preferred metals form the most abundant substrate complex, substrate utilization usually is slowed. 115,145,146,163,226,227 Although several mechanisms have been proposed to account for the reduction in substrate availability and utilization in the presence of various metals, the most general effect comes about when significant metal concentrations reduce substrate availability. This reduction in availability through chemical speciation effects alone occurs when the organic substrate is a strong ligand.…”
Section: Effect Of Actinides On Organic Speciation and Bioavailabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…These include detergent, food, pharmaceutical, cosmetic, metal finishing, photographic, textile and paper industries [1][2][3]. It is also used as a component in decontamination formulation of nuclear reactors and in nuclear waste processing [4,5].…”
Section: Introductionmentioning
confidence: 99%